Improving Early Childhood Learning Outcomes Through Active Play and Exploration - Ningsi, Ayu; Nurhidayah, Nurhidayah; Nurfadillah, Nurfadillah (Educia Journal, 2025)
This qualitative study explores the impact of active play and exploration on early childhood learning outcomes, focusing on three early childhood education centers in Makassar City. Employing a case study design, the research utilized participant observations, semi-structured interviews, focus group discussions, and document analysis to gather comprehensive insights. The findings reveal that active play significantly fosters cognitive development by enhancing problem-solving, critical thinking, and creativity. Social and emotional development were also evident as children engaged in collaborative activities, fostering teamwork, empathy, and self-regulation. Educators played a critical role in facilitating meaningful play experiences through structured guidance and adaptive strategies, while parents highlighted the importance of play in extending learning beyond the classroom. This study addressed gaps in the literature by providing context-specific evidence of the effectiveness of play-based learning in a cultural setting where traditional rote-learning approaches dominate. The findings emphasize the need for a balanced approach that incorporates both child-led and teacher-facilitated play, ensuring alignment with developmental goals. Furthermore, the study underscores the importance of collaboration between educators and families to optimize the benefits of play-based learning. The implications of this study suggest that policymakers and educators should prioritize active play as an integral component of early childhood curricula. By doing so, they can promote holistic child development and create enriched learning environments that nurture lifelong skills.